Chromato-mass-spectroscopic research of chemical composition of Elaeagnus angustifolia L. - O. I. Panasenko; V. I. Mozul; O. M. Denysenko; I. I. Aksonova; T. V. Oberemko (Zaporozhye State Medical University, 2021)
The aim of the work was chromato-mass-spectroscopic research of chemical composition of Elaeagnus angustifolia L. fruits and leaves and identifying further prospects for the use of this plant in medicine. Materials and methods. Raw materials of Elaeagnus angustifolia L. were selected as objects of study. The tincture was obtained by maceration and the raw material was extracted with methyl alcohol at room temperature for 10 days according to the method of making tinctures. The study of the chemical composition of Elaeagnus angustifolia L. was carried out using gas chromatograph Agilent 7890B GC System (Agilent, Santa Clara, CA, USA) with mass spectrometric detector Agilent 5977 BGC/MSD (Agilent, Santa Clara, CA, USA) and chromatographic column DB-5ms (30 m × 250 mkm × 0,25 mkm). Results. 23 compounds (1 in the isomeric state) in fruits and 20 compounds (2 in the isomeric state) in the leaf of Elaeagnus angustifolia L. were identified. The main components of fruits were sitosterol (phytosterols) - 12.53 %, propyl acetate (esters of carboxylic acids) - 12.60 %, chamazulene (terpenes) - 11.97 % and palmitic acid (fatty acids) - 8.28 %. The main component of leaves were sitosterol (phytosterols) - 17.57 %, 1-(2-hydroxy-5-methylphenyl)-ethanone (ketone) - 8.35 %, phytol (terpenes) - 6.10 %. It is known from the literature that chamazulene has antioxidant, antinociceptive, cytotoxic activity. Sitosterol has anti-inflammatory and antidiabetic activity. Hexadecanoic (palmitic) acid has antimicrobial, antidiabetic and antioxidant properties. Phytol is characterized by a wide range of biological action - antimicrobial, antinociceptive, anti-inflammatory, antioxidant and cytotoxic. Conclusions. Based on the above, the olive can be considered as a source of antimicrobial, antinociceptive, anti-inflammatory, antioxidant, antidiabetic and cytotoxic drugs.